Education Moderates the Relationship Between Spirituality with Quality of Life and Stress Among Malay Muslim Women with Breast Cancer - Saeed Pahlevan Sharif (Journal of religion and health, 2019)
The purpose of this study was to investigate the relationship between spirituality with quality of life and stress of Malay Muslim breast cancer patients in Malaysia. In addition, the moderating role of education on this relationship was examined. Participants consisted of 145 conveniently selected Malay breast cancer patients. The results indicated that the more spiritual respondents reported a higher level of quality of life and lower level of stress. Moreover, education weakened the relationship between spirituality with quality of life and stress.